Occurrence and antimicrobial resistance of Salmonella strains from food of animal origin in southern Italy - Proroga, Yolande T R; Capuano, Federico; Carullo, Maria Rosaria; La Tela, Immacolata; Capparelli, Rosanna; Barco, Lisa; Pasquale, Vincenzo (Folia microbiologica, 2016)
Six hundred fourteen strains of Salmonella enterica were isolated from 16,926 samples of food of animal origin collected in southern Italy from 2003 to 2012. The isolates were identified, serotyped, and challenged against 15 antibiotics according to the protocol defined at national level for veterinary isolates of Salmonella (EnterVet surveillance network). Salmonella serotypes Typhimurium, Hadar, Enteritidis, Derby, and 4,[5],12:i:- were those most frequently isolated. The widest resistances were recorded towards sulfonamides (69 % of the isolates), trimethoprim-sulfamethoxazole (52 % of the isolates), and tetracycline (51 % of the isolates). The rate of multidrug resistance of the isolates decreased significantly from the first 5 years of the study period (82.6 %) to the last 5 years (54.3 %).
Keywords: Animals; Food Microbiology; Prevalence; mikrobiální testy citlivosti; Serotyping; lidé; Italy; Anti-Bacterial Agents; Itálie; salmonelová infekce u zvířat; bakteriální léková rezistence; potravinářská mikrobiologie; prevalence; Microbial Sensitivity Tests; Salmonella Infections, Animal; zvířata; antibakteriální látky; Drug Resistance, Bacterial; sérotypizace; Salmonella enterica; Humans